Linguistic Features of Online Scam Messages: A Forensic Analysis of Deceptive Communication Language - Pradesi, Deliana; Marlianingsih, Noni (JEdu: Journal of English Education, 2025)
This research investigates the linguistic features commonly used in online scam messages from a forensic linguistic perspective. The researcher uses a qualitative descriptive approach to analyze twenty scam messages collected from SMS, WhatsApp, and email platforms. The data reveal recurring patterns of deceptive language, including impersonation of official institutions, expressions of urgency, persuasive tone, and call-to-action strategies. These linguistic features are used intentionally by scammers to manipulate victims and create a false sense of trust or fear. The findings highlight how language functions as a tool of deception in digital fraud, offering valuable insights for digital literacy education and forensic investigation. This research contributes to understanding deceptive communication and the practical application of forensic linguistics in combating online scams.